Precision Sensorimotor Control in Aging FMR1 Gene Premutation Carriers - McKinney, Walker S.; Wang, Zheng; Kelly, Shannon; Khemani, Pravin; Lui, Su; White, Stormi P.; Mosconi, Matthew W. (Frontiers in Integrative Neuroscience, 2019)
Background: Individuals with premutation alleles of the FMR1 gene are at risk of developing Fragile X-associated Tremor/Ataxia Syndrome (FXTAS), a neurodegenerative condition affecting sensorimotor function. Information on quantitative symptom traits associated with aging in premutation carriers is needed to clarify neurodegenerative processes contributing to FXTAS. Materials and Methods: 26 FMR1 premutation carriers ages 44-77 years and 31 age-matched healthy controls completed rapid (2 sec) and sustained (8 sec) visually guided precision gripping tasks. Individuals pressed at multiple force levels to determine the impact of increasing the difficulty of sensorimotor actions on precision behavior. During initial pressing, reaction time, the rate at which individuals increased their force, the duration of pressing, and force accuracy were measured. During sustained gripping, the complexity of the force time series, force variability, and mean force were examined. During relaxation, the rate at which individuals decreased their force was measured. We also examined the relationships between visuomotor behavior and cytosine-guanine-guanine (CGG) repeat length and clinically rated FXTAS symptoms. Results: Relative to controls, premutation carriers showed reduced rates of initial force generation during rapid motor actions and longer durations of their initial pressing with their dominant hand. During sustained force, premutation carriers demonstrated reduced force complexity, though this effect was specific to younger premutation carries during dominant hand pressing and was more severe for younger relative to older premutation carriers at low and medium force levels. Increased reaction time and lower sustained force complexity each were associated with greater CGG repeat length for premutation carriers. Increased reaction time and increased sustained force variability were associated with more severe clinically rated FXTAS symptoms. Conclusions: Overall our findings suggest multiple sensorimotor processes are disrupted in aging premutation carriers, including initial force control guided by feedforward mechanisms and sustained sensorimotor behaviors guided by sensory feedback control processes. Results indicating that sensorimotor issues in aging premutation carriers relate to both greater CGG repeat length and clinically rated FXTAS symptoms suggest that quantitative tests of precision sensorimotor ability may serve as key targets for monitoring FXTAS risk and progression.